Evaluation of different damage initiation and growth criteria in the cohesive zone modelling analysis of single-lap bonded joints - Rocha, Ricardo Jorge Braga da (2017)
Adhesively-bonded joints are extensively used in several fields of engineering. Cohesive Zone Models (CZM) have been used for the strength prediction of adhesive joints, as an add-in to Finite Element (FE) analyses that allows simulation of damage growth, by consideration of energetic principles [1]. A useful feature of CZM is that different shapes can be developed for the cohesive laws, depending on the nature of the material or interface to be simulated, allowing an accurate strength prediction. On the other hand, different simulation conditions, and damage initiation and growth criteria, are available for use in CZM analyses to provide the mixed-mode behaviour required to analyse these structures, having as basis the pure tensile and shear CZM laws. Thus, it is highly relevant to understand in detail the influence of these different conditions on the outcome of the simulations. This work studies the influence of different conditions used in CZM simulations to model a thin adhesive layer in single-lap adhesive joints under a tensile loading, for an estimation of their influence on the strength prediction under different geometrical and material conditions. Validation with experimental data is considered. A comprehensive evaluation is performed, considering adhesives ranging from brittle (Araldite® AV138) to highly ductile (Sikaforce® 7752). An adhesive with moderate ductility, the Araldite® 2015, is also considered. Overlap lengths (LO) between 12.5 and 50 mm were also equated. Different simulation conditions were performed and analysed, in which regards to: variation of the elastic stiffness of the cohesive law, decoupling of the loading modes, evaluation of different law shapes, variation of the cohesive parameters and consideration of several damage initiation and growth criteria. The analysis carried out in this dissertation allowed to conclude that CZM is a powerful technique for strength prediction of bonded joints, provided that the modelling conditions are properly defined. The influence of varying conditions to the standard ones was also assessed, showing that erroneous results can be obtained if the choice of the modelling conditions is not the most suitable for the problem.